Neurosensory and vascular function after 14 months of military training comprising cold winter conditions - Carlsson, Daniel; Pettersson, Hans; Burström, Lage; Nilsson, Tohr; Wahlström, Jens (Scandinavian Journal of Work, Environment & Health, 2016)
' ' OBJECTIVE ': 'This study aimed to examine the effects of 14 months of military training comprising cold winter conditions on neurosensory and vascular function in the hands and feet. ' ' METHODS ': 'Military conscripts (N=54) were assessed with quantitative sensory testing comprising touch, temperature, and vibration perception thresholds and finger systolic blood pressure (FSBP) after local cooling and a questionnaire on neurosensory and vascular symptoms at both baseline and follow-up. Ambient air temperature was recorded with body worn temperature loggers. ' ' RESULTS ': 'The subjects showed reduced sensitivity to perception of touch, warmth, cold and vibrations in both the hands and feet except from vibrotactile perception in digit two of the right hand (right dig 2). Cold sensations, white fingers, and pain/discomfort when exposed to cold as well as pain increased in both prevalence and severity. There were no statistically significant changes in FSBP after local cooling. ' ' CONCLUSION ': 'Fourteen months of winter military training comprising cold winter conditions reduced sensation from touch, warmth, cold, and vibrotactile stimulus in both hands and feet and increased the severity and prevalence of symptoms and pain. The vascular function in the hands, measured by FSBP after local cooling, was not affected.
Keywords: cold; cold temperature; cold winter condition; military; military personnel; military training; neurosensory function; old hypersensitivity; sensory threshold; Sweden; vascular function; winter